DEHUMANISATION AND OBJECTIFICATION: LESSONS FROM PRAJWAL PARAJULY’S “THE CLEFT” - Sitohang, Susanne Andrea H. (International Journal of Research -GRANTHAALAYAH, 2021)
In the current world of globalism and multiculturalism and the face of radicalism and terrorism, it is deemed necessary to prepare our students better to face today’s world challenges to guide students to accept differences among them. Therefore, it is considered necessary to unravel their sense of humanity, being aware of ideas such as objectification and to introduce students to the idea that we, humans, despite our different beliefs, ideals, political views, and religions, share common feelings, desires, and needs. People come in different shapes, , and they all have their deficiencies. How do students deal with the injustice, the inhumanity around them? Do they understand acts of objectification and taking place in the world? Do they understand the concepts? What are their ideas of the two terms related to humanity? Understanding these two keywords will help students unravel within them some sense of humanity. This project highlights efforts to introduce students to a work of literature entitled “The Cleft” written by a Nepalese writer . The students read the story and are expected to uncover their sense of humanity by understanding the concepts of objectification and . What lessons can students draw after reading the story? After being introduced to the story and the concepts, students are expected to produce their art project as a reflection and reaction to the story and the ideas embedded in it.